2009
DOI: 10.1016/j.soilbio.2009.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Response of fungal and actinobacterial communities to water-level drawdown in boreal peatland sites

Abstract: We used PCR-DGGE fingerprinting and direct sequencing to analyse the response of fungal and actinobacterial communities to changing hydrological conditions at 3 different sites in a boreal peatland complex in Finland. The experimental design involved a shortterm (3 yrs; STD) and a long-term (43 yrs; LTD) water-level drawdown. Correspondence analyses of DGGE bands revealed differences in the communities between natural sites representing the nutrient-rich mesotrophic fen, the nutrient-poorer oligotrophic fen, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
37
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 67 publications
7
37
2
Order By: Relevance
“…Study on the relationship of soil water contents and microbial functional genes indicated that increased soil moisture rapidly and distinctly changed soil AOA abundances in two temperate forest soils [22]. However, contrary to our present study, it was also observed that fungal and actinobacterial community changes due to short-and long-term water-level changes at three different sites in a boreal peatland complex, indicating that fungal community responds to persistent water-level drawdown, whereas actinobacterial community was less sensitive to hydrological change of short-term groundwater depth drawdown [55]. The interaction between abiotic and biotic factors affects microbial community structure in the natural environment, with effects of plant species on fungal community structure being statistically significant; effects of moisture on bacterial community structure were also significant [35,52].…”
Section: Discussioncontrasting
confidence: 99%
“…Study on the relationship of soil water contents and microbial functional genes indicated that increased soil moisture rapidly and distinctly changed soil AOA abundances in two temperate forest soils [22]. However, contrary to our present study, it was also observed that fungal and actinobacterial community changes due to short-and long-term water-level changes at three different sites in a boreal peatland complex, indicating that fungal community responds to persistent water-level drawdown, whereas actinobacterial community was less sensitive to hydrological change of short-term groundwater depth drawdown [55]. The interaction between abiotic and biotic factors affects microbial community structure in the natural environment, with effects of plant species on fungal community structure being statistically significant; effects of moisture on bacterial community structure were also significant [35,52].…”
Section: Discussioncontrasting
confidence: 99%
“…High abundances of Proteobacteria and Actinobacteria were found by Sun et al (2014) in an SSF; however, in our sites, Actinobacteria comprised only a minority of the total microbial community. This discrepancy can be explained by the different sampling design used by Sun et al (2014), who sampled only the surface layer of peat, where Actinobacteria participate in the aerobic decomposition of litter (Peltoniemi et al, 2009). Members of this phylum can produce extracellular enzymes and have enzymatic capabilities comparable with those of fungi.…”
Section: Bacterial Groups and Their Functionsmentioning
confidence: 99%
“…Mires can be roughly divided into two categories according to their relationship with groundwater: fens are in direct contact with groundwater and thereby receive nutrients from surrounding mineral soils and from rain water, whereas bogs receive nutrients only from rain water (Rydin and Jeglum 2006). This relationship is reflected in several peat characteristics (decomposition rates, vegetation, microbial communities), which greatly dictate the response of a peatland to land-use changes (e.g., Minkkinen et al 1999;Jaatinen et al 2007;Peltoniemi et al 2009Peltoniemi et al , 2012. Also the difference in the supply of the mineral and organic nutrients has a plausible effect on the vegetation and thus on the changes in soil decomposition.…”
Section: Introductionmentioning
confidence: 99%